Trematodes from Greenland. - Brinkmann, August JR. (Meddelelser om Grønland, 1975)
The present investigation deals with trematodes from Greenland - mainly from fishes. Previous investigations in this field have been reviewed and historical and biological commented upon. The present material was mainly collected personally in 1962 at Godhavn (W. Greenland). Of the until then known 20 species from Greenland, 11 species were refound and a further 19 species were encountered as new to the area - hereof 2 nova species. Where necessary further descriptions have been given with systematic discussions based upon anatomy. Further, appropriate lists of trematodes with their hosts, and hosts with their trematodes have been given.